Complexidade de habitat determinando padrões de aninhamento e turnover na comunidade de algas perifíticas. - Osório, Nicolli Cristina (2017)
Considering that habitat complexity is directly linked to the maintenance of biodiversity in aquatic ecosystems, we carried out an field experiment to study the community structure of periphytic algae (richness, biomass, density and diversity) in artificial substrates with different degrees of complexity. We expected that greater structural complexity elevates the attributes of the periphytic community. We also evaluated whether the differences in species composition between substrates were the result of species turnover and/or nestedness. The experiment was carried out in situ, in a lagoon of the Upper Paraná River floodplain. Artificial macrophytes with different complexities were randomly incubated near a bank of natural macrophytes and removed after colonization of the periphyton for qualitative and quantitative analysis. The richness and diversity of species for both substrates did not differ. However, the biomass (chl a) and density of species differed between substrate types, with high biomass and density in the complex substrates. This result shows that although the source of propagules is the same, complex substrates provide space for a greater number of organisms, and that more simplified substrates alter the abundance of species. Our results also indicated that both nestedness and turnover affected the community structure of periphytic algae. Nestedness differed between simple and complex structures only when species abundance was considered; distinctly, species turnover was significantly different only when species occurrence was considered. Thus, we highlight the importance of habitat complexity in determining patterns of beta diversity (turnover and nestedness) allied to species abundance data for structuring the periphytic community.